RIDGE PRESERVATION USING OPEN BARRIER MEMBRANE TECHNIQUES AND FREE GINGIVAL GRAFTS: A RANDOMIZED CONTROLLED TRIAL - Ralitsa Yotsova (Romanian Journal of Oral Rehabilitation)
Background: Tooth extraction leads to a cascade of processes causing alveolar bone resorption and difficulties in subsequent dental rehabilitation. Ridge preservation (RP) involves different strategies, such as atraumatic extraction, immediate implants, and guided tissue regeneration. Aim of the study: This study aims to compare the influence of three different RP methods (with a dense polytetrafluoroethylene membrane (d-PTFE), with a d-PTFE membrane and platelet-rich plasma (PRP), and socket sealing with a free gingival graft (FGG)). Materials and methods: This randomized controlled trial was conducted at the Medical-Dental Centre at the Medical University of Varna, Bulgaria for the period 06/27/2022 – 04/20/2023. Eighty patients were randomly allocated (1:1:1:1) to one of the experimental groups or a control group without ARP. Results: The ARP methods observed in this trial successfully reduced the vertical post-extraction resorption, with the open barrier techniques being superior to the socket sealing with FGGs. Conclusion: The vertical loss of the buccal wall depended on its width and the type of socket management, with the latter being the determining factor. The three methods significantly compensated for the vertical loss of the thin socket walls but did not completely neutralize the influence of the wall width.